1998
DOI: 10.1177/074823379801400501
|View full text |Cite
|
Sign up to set email alerts
|

ATSDR Evaluation of Health Effects of Chemicals. V. Xylenes: Health Effects, Toxicokinetics, Human Exposure, and Environmental Fate

Abstract: Xylenes, or dimethylbenzenes, are among the highest-volume chemicals in production. Common uses are for gasoline blending, as a solvent or component in a wide variety of products from paints to printing ink, and in the production of phthalates and polyester. They are often encountered as a mixture of the three dimethyl isomers, together with ethylbenzene. As part of its mandate, the Agency for Toxic Substances and Disease Registry (ATSDR) prepares toxicological profiles on hazardous chemicals found at Comprehe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 443 publications
(687 reference statements)
0
10
0
Order By: Relevance
“…The organic layer was washed twice with an equal volume of water, once with 10 m KOH and once with 20 m KOH to remove the phenolic products, and three times more with water. After drying over anhydrous MgSO 4 and distillation at 50 8C, the majority of the solvent was gently evaporated prior to NMR spectroscopy. Silica chromatography was used as a final purification step prior to UV/Vis spectroscopy, the mobile phase being hexane/ethyl acetate (8:2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The organic layer was washed twice with an equal volume of water, once with 10 m KOH and once with 20 m KOH to remove the phenolic products, and three times more with water. After drying over anhydrous MgSO 4 and distillation at 50 8C, the majority of the solvent was gently evaporated prior to NMR spectroscopy. Silica chromatography was used as a final purification step prior to UV/Vis spectroscopy, the mobile phase being hexane/ethyl acetate (8:2).…”
Section: Methodsmentioning
confidence: 99%
“…The commonest reaction type is the conversion of an unreactive carbonÀhydrogen bond to the corresponding alcohol, but epoxidation of olefinic linkages, dehydrogenation and dealkylation are also known. [1,2] CYP enzymes play roles in numerous metabolic pathways, both catabolic and anabolic, notably those relating to the biosynthesis of hormones and antibiotics [2,3] and the breakdown of xenobiotics, such as the benzene, toluene, ethylbenzene and xylene [4] (BTEX) family of contaminants. [5] P450 BM3 (CYP102A1), a sub-terminal fatty-acid hydroxylase from Bacillus megaterium, has been widely researched, partly because it is catalytically self-sufficient and water-soluble.…”
Section: Introductionmentioning
confidence: 99%
“…Plommet (1972) used xylene at a concentration of 0·1% in slurry for inactivation of Brucella abortus . Toxic effects in humans due to exposure to xylene include eye and respiratory tract irritation, central nervous system changes and damage to the liver and kidneys (Fay et al . 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The toxicology of xylenes has been described in several reviews (Carpenter et al, 1975;ECETOC, 1986;Low et al, 1989;Fay et al, 1998;US EPA, 2003) and, in general, the studies have indicated little toxicity associated with these solvents. However, xylenes belong to the aromatic solvents, some of which, like toluene, styrene or ethylbenzene, show a characteristic toxicity on the auditory system of the rat characterized by an irreversible hearing loss, as measured by behavioural or electrophysiological methods, associated with damage to hair cells in the cochlea of the exposed animals (Pryor et al, , 1984(Pryor et al, , 1987Rebert et al, 1983;Sullivan et al, 1988;Johnson and Canlon, 1994;Yano et al, 1992;Campo et al, 1997;Cappaert et al, 1999Cappaert et al, , 2000Cappaert et al, , 2001Cappaert et al, , 2002.…”
Section: Introductionmentioning
confidence: 97%